2019
DOI: 10.3390/chemengineering3040081
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity, Viscosity, Spectroscopic Properties of Organic Sulfonic Acid solutions in Ionic Liquids

Abstract: Sulfonic acids in ionic liquids (ILs) are used as catalysts, electrolytes, and solutions for metal extraction. The sulfonic acid ionization states and the solution acid/base properties are critical for these applications. Methane sulfonic acid (MSA) and camphor sulfonic acid (CSA) are dissolved in several IL solutions with and without bis(trifluoromethanesulfonyl)imine (HTFSI). The solutions demonstrated higher conductivities and lower viscosities. Through calorimetry and temperature-dependent conductivity ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Further lowering of catalyst led to reduced amount of product (entries 3 and 4). Using hexafluoroisopropanol (p K a =9.3 in H 2 O) [21] as solvent instead of AcOH (p K a =4.72 in H 2 O) [22] resulted in just 9 % conversion from 1a to 2a (entry 5). Use of trifluoroacetic acid (p K a =−0.3 in H 2 O) [23] also led to selective reduction of the A‐ring of 1a in excellent yield (entry 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further lowering of catalyst led to reduced amount of product (entries 3 and 4). Using hexafluoroisopropanol (p K a =9.3 in H 2 O) [21] as solvent instead of AcOH (p K a =4.72 in H 2 O) [22] resulted in just 9 % conversion from 1a to 2a (entry 5). Use of trifluoroacetic acid (p K a =−0.3 in H 2 O) [23] also led to selective reduction of the A‐ring of 1a in excellent yield (entry 6).…”
Section: Resultsmentioning
confidence: 99%
“…To achieve selective amine formation, we revisited alternative acids. Pleasingly, we found that using 3 equivalents of methanesulfonic acid (MsOH, p K a =−2.6 in H 2 O) [22] in i PrOH allowed for selective formation of 6a in 90 % yield.…”
Section: Resultsmentioning
confidence: 99%
“…The above problem was readily resolved by loading the silica gel with water acidified using a small amount of a non-volatile, strong organic acid, such as camphor sulfonic acid, CSA, which has a pK a of ca. 1.2 [31]. In order to test the system with this new additive, the same mass loss vs. applied pressure experiments as described above for the 61 wt% silica gel/PTFE powder mixture were then carried out using instead a silica gel powder loaded with 61wt% of water acidified with CSA and PTFE powder mix, i.e., the same mix as used to prepare the typical pressed discs described in Section 2.2.1 and used in the HPP indicator illustrated in Figure 1.…”
Section: The Acidified Water-releasing Pressed Discmentioning
confidence: 99%
“…They have many advantages, such as chemical and thermal stability, low flammability, and low vapor pressures [1]. Because of these advantages, ionic liquids have been applied in organic reactions as solvents, catalysts, and liquid thermal storage fluids [2,3]. Ionic liquids are expensive.…”
Section: Introductionmentioning
confidence: 99%